Philippine industry and pollution control legislation - Ross, Marlay (1976)
Since industrialization is seen as the all important remedy to most of the economic ills of the developing countries in the Third World, it has easily gained numerous advocates from both
the private and public sectors. The almost unquestionning acceptance of the industrialization ideology" has resulted in little attention to its possible adverse effects on the environment. Most Philippine industries, except for a few selected firms, have managed to avoid pollution control legislation by 1) arguing that industry is vital to the national well-being, 2) involving the sentiment of awa (pity), 3) deflecting blames from industry to the public, 4) creating a favorable public relations image, 5) fighting legal battles, 6) gaining access to the policy processes, 7) indefinitely delaying compliance, 8) outright deception and non-compliance and 9) attempting to shift the cost of compliance from industry to the government. This article discusses each of these strategies and looks into their possible consequences on Philippine environmental control programs.
Keywords: Industrial policy -- Environmental aspects; Industrialization and the environment; Industrialization -- Social aspects